2014
DOI: 10.1186/1472-6874-14-107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a group based cognitive behavioural therapy programme for menstrual pain management in young women with intellectual disabilities: protocol for a mixed methods controlled clinical trial

Abstract: BackgroundMenstrual pain which is severe enough to impact on daily activities is very common amongst menstruating females. Research suggests that menstrual pain which impacts on daily functioning may be even more prevalent amongst those with intellectual disabilities. Despite this, little research attention has focused on pain management programmes for those with intellectual disabilities.The aims of this pilot study were to develop and evaluate a theory-based cognitive behavioural therapy (CBT) programme for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Ten papers were identified for final qualitative analysis and extracted characteristics are summarised in Table I. In total, 17 screened papers were excluded for the following reasons: literature review article (n ¼ 2) (Albanese and Hopper, 2017;Jeffery et al, 2013), approach not in line with modern practice (n ¼ 2) (Huovinen, 1993;Kaminer et al, 1988), abstract only (n ¼ 1), (Ibralic et al, 2010), limited relevance for management of PMS (n ¼ 12) (Arvio et al, 2009;Backeljauw et al, 2004;Chou and Lu, 2009;Dickson et al, 2018;Greenwood and Wilkinson, 2013;Kennedy et al, 2014;Pikora et al, 2014;Roxburgh and West, 1973;Sinnema et al, 2011;Tracy et al, 2016;Wilkinson and Ceretto, 2008;Wingfield et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten papers were identified for final qualitative analysis and extracted characteristics are summarised in Table I. In total, 17 screened papers were excluded for the following reasons: literature review article (n ¼ 2) (Albanese and Hopper, 2017;Jeffery et al, 2013), approach not in line with modern practice (n ¼ 2) (Huovinen, 1993;Kaminer et al, 1988), abstract only (n ¼ 1), (Ibralic et al, 2010), limited relevance for management of PMS (n ¼ 12) (Arvio et al, 2009;Backeljauw et al, 2004;Chou and Lu, 2009;Dickson et al, 2018;Greenwood and Wilkinson, 2013;Kennedy et al, 2014;Pikora et al, 2014;Roxburgh and West, 1973;Sinnema et al, 2011;Tracy et al, 2016;Wilkinson and Ceretto, 2008;Wingfield et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Current UK guidelines recommend that cognitive behavioural therapy (CBT) should routinely be offered to patients presenting with severe PMS (Green et al, 2017). There have been successful reports of modified CBT being an effective treatment of depression, anxiety and anger management in patients with mild-moderate ID (Busse et al, 2009;Kennedy et al, 2014). This has been explored by Kennedy et al (2014) in the management of menstrual pain in women with ID.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case series, the authors of the treatment manual reported some preliminary evidence of the effectiveness of the programme (McManus and McGuire, 2014 ) but noted that more research is needed, including controlled clinical trials. Subsequently, a trial protocol has been registered (Kennedy et al, 2014 ) to evaluate the effectiveness of the Feeling Better programme for management of menstrual pain in young women with an intellectual disability. Treatment outcomes have not yet been reported but will be important as the first controlled trial to evaluate psychological management of pain for people with an intellectual disability.…”
Section: Modifying Pain Experience In People With Down Syndromementioning
confidence: 99%
“…7,12 To date, only two studies have examined psychological interventions focused on pain in individuals with a diagnosis of ID, both using cognitive behavioral therapy to teach self-management strategies for chronic pain. 13,14 These studies included individuals who were high functioning, with good verbal communication skills, and did not involve people with ASD and/or moderate ID. There is an ongoing need for research on interventions for people with more severe cognitive impairments and other complex presentations.…”
mentioning
confidence: 99%